Three new Macropsini (Hemiptera: Cicadellidae) leafhopper species from Australia - Yang, Liyuan; Dietrich, Christopher H.; Zhang, Yalin (Zootaxa, 2017)
Three new species, Macropsella recta, Toropsis minuspina and Varicopsella apecurvata spp. nov. are described and illustrated from Australia.       Leafhoppers of the subfamily Macropsinae are found abundantly in the Holarctic, Oriental and Australian regions (Linnavuori, 1978) and have been collected from around the world, except for Antarctica, Oceania and South America (Hamilton, 1980). Both Hamilton (1980) and Evans (1966) suggested that there were likely a myriad of uncollected and undescribed species in Australia alone and Evans (1971) commented that the Macropsinae are possibly more abundant in Australia than anywhere else in the world. Day and Fletcher (1994) listed 45 macropsine species in eight genera and mentioned that the Australian fauna needs “a thorough examination to establish the generic affinities of the species…”. In her unpublished doctoral dissertation, Semeraro (2014) recently completed a revision and phylogeny of the Australian fauna, documenting an additional 50 undescribed species and proposing changes to the generic classification, but this work has not yet been published. The new Australian species described herein, representing three genera, one not previously recorded in Australia, were not included in Semeraro’s (2014) dissertation.Study of samples recently collected from Australia revealed the presence of 3 new species, representing the genera Macropsella Hamilton, Toropsis Hamilton and Varicopsella Hamilton.Macropsella was established by Hamilton (1980) with Macropsis saidora Evans, 1971 as the type species. Five Macropsis species describeded by Evans (1971), one Macropsis species described by Kirkaldy (1907) and new species Macropsella complicata Hamilton (1980) were previously included in this genus. The seven species of this genus are known only from New Guinea and Northern Australia. Members of this genus can be distinguished by their usually white spotted tegminal veins, tapered male pygofer and laterally directed short ventral pygofer spines.Toropsis was established by Hamilton (1980) with Oncopsis balli Kirkaldy, 1907 as the type species. Six Oncopsis species (Evans, 1935, 1941) and three Macropsis species (Evans, 1971; Metcalf, 1966) were transferred to this genus by Hamilton (1980). So far, ten species recorded in this genus, and all of these species are recorded only from Australia. Toropsis can be distinguished by the wide face, small and flat front, inflated pronotum, unarmed male pygofer and relatively small dorsal connectives.Varicopsella was established by Hamilton (1980) for seven species from the Oriental region, with Macropsis breakeyi Merino, 1936 as its type species. More recently, Li et al. (2014) added a new species and subgenus Varicopsella (Multispinulosa) hamiltoni from China, but this species appears to be incorrectly placed in Varicopsella. Yang et al. (2016) added V. odontoida from Thailand. This genus can be distinguished by the depressed head, fused lora and frontoclypeus, and the two-jointed dorsal connective of the male.